Use of Cystorelin® and artificial insemination in repeat-breeding beef heifers after estrous synchronization - J.P. Holz; P.L. Houghton; M.F. Spire (Kansas Agricultural Experiment Station Research Reports, 1993)
Gonadotropin-releasing hormone (GnRH) was administered to a group of 13- to 14- month-old Angus and Angus crossbred repeat-breeding heifers at the time of the second or third artificial insemination to determine its effect on conception rates. Little benefit was derived from the use of GnRH at either second or third service in highly developed repeat-breeding heifers.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Gonadotropin-releasing hormone; Repeat breeders; Conception rate; Beef heifers